Four freshwater dematiaceous hyphomycetes in Sordariomycetes with two new species of Parafuscosporella - Yang, Hao; Dong, Wei; Yu, Xian-Dong; Bhat, D. Jayarama; Boonmee, Saranyaphat; Zhang, Huang (Phytotaxa, 2020)
A collection of lignicolous freshwater fungi in the Greater Mekong Subregion resulted in four interesting dematiaceous hyphomycetes with similar morphology. The taxa had sporodochial colonies, micronematous to semi-macronematous conidiophores and subglobose, ellipsoidal to broadly pyriform, 0–1-septate, dark brown to black conidia. Based on morphological characters and phylogenetic analyses of combined LSU, SSU, ITS and RPB2 sequence data, Parafuscosporella aquatica sp. nov., P. pyriformis sp. nov., Conioscypha tenebrosa and Vanakripa minutiellipsoidea are identified. Parafuscosporella aquatica and P. pyriformis cluster within Fuscosporellaceae (Fuscosporellales), while C. tenebrosa and V. minutiellipsoidea are placed within Conioscyphales. This is the first report on the phylogenetic placement of Vanakripa. Descriptions and illustrations of the new collections are provided.